The Development of Guidance and Counseling Platform Using Google Sites-based “Friend Story” (Storytelling) Media for College Students at UIN Ar-Raniry - Tengku, Tengku Febri Irwansyah; Elviana, Elviana (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
English: This research aims to develop and test the feasibility of the Google Sites-based "Friends Story" media for Ar-Raniry State Islamic University College Students.  The research method used is Research and Development  (R & D). This research uses the Thiagarajan, Dorothy Semmel, and Melvyn Semmel models. Research and development stages include (1) define, (2) design, (3) develop, and (4) dissemination. The subjects of this research were College Students at Ar-Raniry State Islamic University with a sample of 6 respondents. The research instrument used was an expert validation sheet with qualitative descriptive data analysis techniques. The research results show that the average score from material experts is 88.2% and the average score from media experts is 87.5%. Meanwhile, the average value of lecturer responses via questionnaire was 93.3% and the average College Student response was 87%. From these results, it can be concluded that the development of Google Sites-based “story-friend” media is in the “Very Feasible” category and can be used. Indonesia: Tujuan penelitian ini adalah untuk mengembangkan  dan menguji kelayakan media “Teman bercerita” berbasis Google Sites mahasiswa Universitas Islam Negeri Ar – Raniry .  Metode penelitian yang digunakan adalah Penelitian dan Pengembangan. Penelitian ini menggunakan model Thiagarajan, Dorothy Semmel, dan Melvyn Semmel. Tahapan penelitian dan pengembangan meliputi (1) define, (2) design, (3) develop, dan (4) dissemination. Subyek penelitian ini adalah mahasiswa Universitas Islam Negeri Ar – Raniry dengan sampel berjumlah 6 responden. Instrumen penelitian yang digunakan adalah lembar validasi ahli dengan teknik analisis data deskripsi kualitatif. Hasil penelitian menunjukkan bahwa nilai rata-rata dari ahli materi sebesar 88,2% dan nilai rerata dari ahli media adalah 87,5%. Sementara itu, nilai rata-rata dari respon dosen melalui angket adalah 93,3% dan rerata respon mahasiswa sebesar 87%. Dari hasil ini bisa disimpulkan bahwa pengembangan media “Friend Story ” berbasis Google Sites masuk dalam kategori “Sangat Layak” dan dapat digunakan.